PERTUMBUHAN SEMAI RHIZOPHORA MUCRONATA PADA LUAS SALURAN TAMBAK WANAMINA YANG BERBEDA - Hadyani M Hanifa; Endah Dwi Hastuti; Rini Budi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
The mangrove forest is a natural resource that is vital to the life of coastal communities, and has experienced the threat of relegation very fast. Seedling growth is important in mangrove conservation in wanamina (silvofishery). This study aimed to examine the growth of mangrove seedlings R. mucronata on different wide of channel ponds. Planting mangrove seedlings carried on channel ponds wanamina (Silvofishery) with a 5 m of length and varies width, that is 1 m; 2 m and 3 m. This research used experimental method with Randomized Design (RBD) conducted for 4 months with the observation period once every two weeks. Mangrove growth was observed are the number of leaves, number of branches, seedling height and stem diameter. Data analysis was performed using Analysis of Variance (ANOVA). The results showed that there was a tendency of better seedling growth in the outlet channel and the channel with 1 m width. Key words: growth, mangrove, silvofishery, seedlings.